GAMBARAN PROGRESSIVE MUSCLE RELAXTATION (PMR) TERHADAP KADAR GLUKOSA DARAH (LITERATURE REVIEW) - Anitha Anitha (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2021)
Diabetes Mellitus (DM) is an increase in glucose levels in the blood or what is known as hyperglycemia, in which the body cannot produce the hormone insulin or use insulin effectively. Non-pharmacological management of DM should be considered as a companion to conventional or medical therapy such as relaxation therapy, there are several types of relaxation therapy, one of which is Progressive Muscle Relaxation (PMR). The benefits of PMR are to reduce the body's oxygen consumption, the body's metabolic rate, the respiratory rate of muscle tension, premature ventricular contractions and systolic blood pressure and brain alpha waves and can increase beta endorphins and function to increase cellular immunity. From the results of the study, it was found that the provision of non-pharmacological therapy of progressive muscle relaxation has an effect on reducing blood glucose levels in type 2 DM clients and has positive implications, namely it can provide a sense of comfort, relax, reduce stress, and can reduce blood glucose levels in the body in DM clients. type 2.